Student Event Information Application (SEIA) using gamification technique / Muhammad Khalis Ramni Abdul Malek - Ramni Abdul Malek, Muhammad Khalis (Faculty of Computer and Mathematical Sciences, 2017)
Organizing event is not an easy task since it requires efficient time management, patience, manage people and take care of the facilities that require for the event. The organizer has to make use the event run smoothly from planning until the end of the event. Software and application are playing a vital role to ease the task of manage event. This application is develop due to the inefficiency of the current method in managing participant list for an event and consume time to record the student’s attendance during the event. This application can help to provide reliable and easier way to spread the event information. This application also reduces the time taken for spread the event information and record the student attendance. This application solves the fake signature problem by students to make false attendance. This application provides features of managing event, managing committee and manage student. Furthermore, this application also includes other features such as lead score, scan attendance and send the attendance list to email. This mobile application was developed based on the Waterfall model that has been modified. The model consists of four phases which are the requirement definition, system design, system implementation and system testing. This mobile application was designed and developed based on the gathered information from requirement definition phase. The design includes the use-case diagram, flowchart diagram, ER diagram, navigation map design, system architecture, and the gamification framework. After the system design phase has completed, the application was developed in Visual Studio Code. The main programming languages are HTML, CSS, typescript, PHP and MyPHPAdmin was the database platform used for this application. The gamification framework consists of mechanism, motive and dynamic. The mechanism used for the application was ranking where the student can view their points and their position in the lead score. The motive of this application was social recognition where the highest points user will get reward and all student can know who have the highest points based on the lead score. The dynamic for this application is the competition between students to gain highest points. Functionality testing was done to verify the application produce expected output. Results show that the application produces the expected output and able to do the management, scan attendance, lead score and other features functions correctly.